The role of attention in decision-making under risk in gambling disorder: An eye-tracking study. (March 2023) - Hoven, Monja; Hirmas, Alejandro; Engelmann, Jan; van Holst, Ruth J.
Highlights: Attention during risky decision-making has scarcely been studied in Gambling Disorder (GD). Patients with GD showed increased gambling and decreased loss aversion. Patients with GD did not show a direct attentional bias towards gains. Attention to gains moderated the effect of gain value on choice to gamble in GD. GD patients with more average attention to gains had an increased influence of gain value on gamble choice. Abstract: Gambling disorder (GD) is a behavioural addiction characterized by impairments in decision-making, favouring risk- and reward-prone choices. One explanatory factor for this behaviour is a deviation in attentional processes, as increasing evidence indicates that GD patients show an attentional bias toward gambling stimuli. However, previous attentional studies have not directly investigated attention during risky decision-making. 26 patients with GD and 29 healthy matched controls (HC) completed a mixed gambles task combined with eye-tracking to investigate attentional biases for potential gains versus losses during decision-making under risk. Results indicate that compared to HC, GD patients gambled more and were less loss averse. GD patients did not show a direct attentional bias towards gains (or relative to losses). Using a recent (neuro)economics model that considers average attention and trial-wise deviations in average attention, we conducted fine-grained exploratory analyses of the attentional data. Results indicate that the average attention for gains in GD patients moderated the effect of gain value on gambling choices, whereas this was not the case for HC. GD patients with high average attention for gains started gambling at less high gain values. A similar trend-level effect was found for losses, where GD patients with high average attention for losses stopped gambling at lower loss values. This study gives more insight into how attentional processes in GD play a role in gambling behaviour, which could have implications for the development of future treatments focusing on attentional training or for the development of interventions that increase the salience of losses.